Futures Literacy Lab for Education: Imagining Complex Futures of Human Settlements at Finland Futures Academy Summer School 2017 - Nicolas A. Balcom Raleigh; Laura Pouru; Ellinoora Leino-Richert; Marjukka Parkkinen; Markku Wilenius (University of Turku, Finland Futures Research Centre, 2022)
This book is published as part the research and education agenda of the UNESCO Chair in Learning Society and Futures of Education (LSFE) held by Professor Markku Wilenius at Finland Futures Research Centre, University of Turku. The aim of the UNESCO Chair in LSFE is to utilize the tools of futures research to increase global futures thinking and well-being. The Futures Literacy Lab for Finland Futures Academy Summer School 2017 was co-organized by the UNESCO Chair in LSFE research team, the Futures of Cities and Communities research team, and the UNESCO Management of Social Transformations Programme.